Association between IL-1A and IL-1B gene polymorphisms with peri-implantitis in a Portuguese population—a pilot study - Cardoso,José Maria; Ribeiro,Ana Clara; Palos,Constança; Proença,Luis; Noronha,Susana; Alves,Ricardo Castro (PeerJ, 2022)
Background Scientific evidence indicates that biological complications in dental implants tend to be concentrated in a subset of individuals, which seems to imply that the host response may play a determining role in implant success. Over the last few decades, several polymorphisms have been studied. Polymorphisms in the interleukin (IL) 1 gene cluster have been associated with periodontitis. There are some similar features in the sequence of immunopathological events in peri-implant and periodontal infections. We aimed to investigate if individuals carrying the genetic single nucleotide polymorphism (SNP) in the IL-1A (rs1800587) and IL-1B (rs1143634) genes are more susceptible to develop peri-implantitis. Methods A cross-sectional analytic pilot study was conducted in 20 Caucasian Portuguese subjects divided into two groups: 10 subjects with peri-implantitis and 10 subjects with peri-implant health (control group). Samples containing cells from the buccal mucosa were stored at −20 °C and later submitted to the DNA extraction process. Genetic analysis was performed using the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analysis. Data were analyzed by using descriptive and inferential statistical methodologies. Results For the IL-1A (−889) gene polymorphism, it was observed that the mutated allele was present in a higher percentage in the peri-implantitis group compared to the control group (30% vs 15% respectively, Fisher’s exact test, p = 0.45). For the IL-1B (+3954) gene polymorphism, it was also observed that the altered allele was present in a higher percentage in the disease group compared to the control group (35% vs 10% respectively, Fisher’s exact test, p = 0.13). The positive genotype (at least one allele with nucleotide sequence changed in both genes) was detected in six patients, five belonging to the disease group and one to the health group. Conclusions Regarding IL-1 gene polymorphisms, there was no statistically significant difference between the health and disease group, however a trend should be highlighted, showing a potential link between the IL-1 genotype and peri-implantitis. More studies are needed to clarify the role of genetic polymorphisms in the development of peri-implantitis.
Keywords: Genetics; Peri-implantitis; Interleukin-1; Single-nucleotide polymorphism; Interleukin-1-genotype; Genetic polymorphisms; Peri-implant disease